VERGİ USUL KANUNU MADDE 10: OLGU VE DİL - (:unkn) unknown (My University, 2013)
Kanuni temsilcilerin şirketlerin vergi borçlarından doğan sorumluluğu Vergi Usul Kanunu Madde 10da belirlenmiştir. Maddenin okunmasında bazı problemler vardır. Çünkü sorumluluk kriterleri yasa koyucu tarafından tanımlanmıştır fakat maddenin yorumu Gelir İdaresi ve Danıştay tarafından yapılmaktadır. Dava olgularında başvurulacak yasal dilin yorumu ve anlamı konusunda genel bir teori yoktur. Bununla birlikte yirminci yüzyılın en büyük filozofu Ludwig Wittgenstein dünya-düşünce-dil arasındaki ilişkilerde yeni bir anlayış getirmiş ve analizini Tractatus Logico-Philosophicus ve Felsefi Soruşturmalarda geliştirmiştir. Bu makale vergi hukukunda olgu ve dil kavramları arasındaki ilişkiyi Wittgensteinın felsefi çalışmalarıyla tartışmaktadır.

The liability of legal representatives arising from tax debts of companies is determined by Article 10 of the Tax Procedure Code. Te reading of the article has some problems because whereas the criteria of liability is defined by the parliament, the provision is intrepreted by the Revenue Administration and the Council of State. Tere is no general theory of the meaning and interpretation of legal language applying to the facts of a case. But still Ludwig Wittgenstein, the greatest philosopher of the 20th century, provided new insights into the relations between world, thought and language and developed his analysis in Tractatus Logico-Philosophicus and Philosop hical Investigations. Tis article dis- cusses the relation between the fact and legal language in the tax law by means of the philosphical works of Wittgenstein.
Article 10 of the Tax Procedure Code: The fact and legal language
Keywords: Hukuk